Chemical vapor deposition of multi-walled carbon nanotubes from nickel/yttria-stabilized zirconia catalysts - Ferlauto, A. S.; De Florio, D. Z.; Fonseca, F. C.; Esposito, V.; Muccillo, R.; Traversa, E.; Ladeira, L. O. (Springer, 2006)
Multi-walled carbon nanotubes (MWNT) were produced by chemical vapor deposition using yttria-stabilized zirconia/nickel (YSZ/Ni) catalysts. The catalysts were obtained by a liquid mixture technique that resulted in fine dispersed nanoparticles of NiO supported in the YSZ matrix. High quality MWNT having smooth walls, few defects, and low amounts of by-products such as amorphous carbon were obtained, even from catalysts with large Ni concentrations (> 50 wt.%). By adjusting the experimental parameters, such as flux of the carbon precursor (ethylene) and Ni concentration, both the MWNT morphology and the process yield could be controlled. The resulting YSZ/Ni/MWNT composites can be interesting due to their mixed ionic-electronic transport properties, which could be useful in electrochemical applications.